Pomen vadbe za moč srednje zadnjične mišice - Jošt, Matija (Šport (Ljubljana), 2018)
The gluteus medius belongs in the category of pelvic girdle muscles. The main function of this muscle is to abduct the hip, while it also helps with the internal nad external rotation of the hip and its flexion and extension. A normal functioning of these muscles is key to ensuring proximal stability in movement of the lower extremities, mainly stabilizing the pelvis in the frontal and transversal plane. A weakened muscle function of gluteus medius is often the cause of irregular biomechanics of lower extremities and often causing the patellofemoral and iliotibial syndrome, and may cause injury to the cruciate ligament due to the valgus in the knee. In our contribution we research and explain the function of gluteus medius and the importance of its strength training. We begin with by introducing the anatomy of gluteus medius and its function. We then go on to describe the importance of strengthening this muscle, and the consequences of its weakening. Then we introduce the exercises which are suitable for strength training, which are divided into those performed in a standing and lying position. Finally, we provide guidelines for including these exercises into training programs.
Keywords: anatomija; srednja zadnjična mišica; šport; vadba za moč; vaje za krepitev